2019
DOI: 10.1016/j.pec.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

How do health professionals decide whether an interpreter is needed for families in neonatal and pediatric units?

Abstract: Highlights Health professionals find it difficult to decide whether an interpreter is needed Health professionals' attitudes and goals affect their decision making about interpreters There is marked variability in the decision-making process individual health professionals use Training is needed, including a decision tool, to assist health professionals' decisions Objective: To examine how health professionals decide whether family members require an interpreter. Methods: 69 health professionals, doctors, nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…Not surprisingly Parker, Lopera, Kalluri, and Kistin (2018) found in their study that the mothers felt more reassured and supported when the exchange was in their native language. If healthcare professionals are uncertain whether an interpreter is needed (Jones, Sheeran, Pines, & Saunders, 2019), this is usually a sign that they do need an interpreter. The purpose of interpreting is ideally to mediate a speaker's ideas to the listener as if they were expressed in the listener's own language (Nailon, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly Parker, Lopera, Kalluri, and Kistin (2018) found in their study that the mothers felt more reassured and supported when the exchange was in their native language. If healthcare professionals are uncertain whether an interpreter is needed (Jones, Sheeran, Pines, & Saunders, 2019), this is usually a sign that they do need an interpreter. The purpose of interpreting is ideally to mediate a speaker's ideas to the listener as if they were expressed in the listener's own language (Nailon, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…When asked, most health professionals note a range of practical barriers (i.e., challenges accessing services outside of business hours, perceived or actual costs, time consuming etc.). Health practitioners also find it difficult to assess whether an interpreter is needed (Jones et al, 2019), though participants in the current study perceived that the health practitioner's attitude to engaging an interpreter may be an additional barrier (i.e., "they just don't want to do it"). We suggest further research is needed to unpack attitudes held by the professionals themselves.…”
Section: Discussionmentioning
confidence: 81%
“…Thus, it seems that some police may also have a narrow view of communication and the role of interpreters. This view has been found in doctors, where the use of interpreters allowed the doctors to tell the patient what would happen, rather than allowing the patient to elicit information from the doctor (Jones et al, 2019). We argue that the two-way flow of information is vital to ensuring accuracy in reports and facilitating the understanding of the woman experiencing RCA.…”
Section: Discussionmentioning
confidence: 82%
“…37 Still, nurses' positive linguistic attitudes tend to change when they experience problems in practice, and consequently practical courses on how to use professional interpreters in healthcare would be useful. 37 Jones et al 38 found that healthcare staff underutilize professional interpreters, even though researchers and policy-makers alike recommend using such services. Practical courses 39 or education and training 40 have been found to possibly improve healthcare staff's negative attitudes toward professional interpreter services.…”
Section: Introductionmentioning
confidence: 99%
“…37 Jones et al. 38 found that healthcare staff underutilize professional interpreters, even though researchers and policy-makers alike recommend using such services. Practical courses 39 or education and training 40 have been found to possibly improve healthcare staff’s negative attitudes toward professional interpreter services.…”
Section: Introductionmentioning
confidence: 99%